Health Literacy: Knowledge and Experience Among Senior Students in a Nursing College - Trixia S. Maduramente; Jeric D. Orendez; Judelle A. Saculo; Angela Louise A. Trinidad; Ryan Michael F. Oducado (Indonesian Nursing Journal of Education and Clinic (INJEC), 2019)
Introduction: Training and education on health literacy must start in the undergraduate nursing program. While nursing schools include health education courses and provide opportunities for nursing students to give healthcare information to individuals in various healthcare settings, there is a dearth of empirical evidence on health literacy in the Philippines. The purpose of this study was to examine the health literacy knowledge and experience of senior nursing students in a College of Nursing in Iloilo City, Philippines. Methods: This study utilized a descriptive crosssectional research design with 160 senior nursing students as participants. Data were gathered using Cormier's (2006) Health Literacy Knowledge and Experience Survey (HL-KES) questionnaire. Descriptive statistical tools, ttest, ANOVA and Pearson'sr were used to analyze the data. Results: Results revealed that majority of senior nursing students had limited health literacy knowledge (M= 13.19) and had moderate health literacy experience (M= 2.50). No significant differences were found in the knowledge and experience according to sex (p>. 05) as well in grade in Health Education course (p>. 05). Knowledge of health literacy was not significantly related to health literacy experience (p>. 05). Conclusions: Health literacy must be given greater emphasis in the undergraduate nursing curriculum. Nursing schools must pay more attention to devising measures in improving nursing students' health literacy competencies.
Keywords: 330; health literacy; health education; nursing students; nursing education